2021
DOI: 10.1093/biolinnean/blab089
|View full text |Cite
|
Sign up to set email alerts
|

Sympatric occurrence of deeply diverged mitochondrial DNA lineages in Siberian geometrid moths (Lepidoptera: Geometridae): cryptic speciation, mitochondrial introgression, secondary admixture or effect ofWolbachia?

Abstract: The divergent sympatric mitochondrial lineages within traditionally recognized species present a challenge regularly faced by taxonomists and evolutionary biologists. We encountered this problem when studying the Siberian geometrid moths, Alcis deversata and Thalera chlorosaria. Within each of these species we found two deeply diverged mitochondrial lineages that demonstrated a level of genetic differentiation exceeding the standard interspecific DNA barcode threshold. Using analyses of nuclear genes, morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…Mitochondrial markers and genomes are especially useful for species identification and delimitation (Reese et al, 2020), for assessing population structure (Flores-Manzanero et al, 2022;Gagneux et al, 1999;Phukuntsi et al, 2021;Serrao et al, 2018;Skovrind et al, 2021), for assessing introgression and admixture (Makhov et al, 2021;Malukiewicz et al, 2021), for monitoring of species assemblages using environmental DNA (Barnes & Turner, 2016;Thomsen & Willerslev, 2015), and for identifying the origin Handling Editor: David Coltman phylogeny based on these samples along with additional published platyrrhine mitogenomes, and use this to assess support for the long-standing riverine barrier hypothesis (RBH), which proposes that river formation was a major driver of speciation in Amazonian primates. Along the Amazon, Negro, and Madeira rivers, we found mixed support for the RBH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial markers and genomes are especially useful for species identification and delimitation (Reese et al, 2020), for assessing population structure (Flores-Manzanero et al, 2022;Gagneux et al, 1999;Phukuntsi et al, 2021;Serrao et al, 2018;Skovrind et al, 2021), for assessing introgression and admixture (Makhov et al, 2021;Malukiewicz et al, 2021), for monitoring of species assemblages using environmental DNA (Barnes & Turner, 2016;Thomsen & Willerslev, 2015), and for identifying the origin Handling Editor: David Coltman phylogeny based on these samples along with additional published platyrrhine mitogenomes, and use this to assess support for the long-standing riverine barrier hypothesis (RBH), which proposes that river formation was a major driver of speciation in Amazonian primates. Along the Amazon, Negro, and Madeira rivers, we found mixed support for the RBH.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial markers and genomes are especially useful for species identification and delimitation (Reese et al, 2020), for assessing population structure (Flores‐Manzanero et al, 2022; Gagneux et al, 1999; Phukuntsi et al, 2021; Serrao et al, 2018; Skovrind et al, 2021), for assessing introgression and admixture (Makhov et al, 2021; Malukiewicz et al, 2021), for monitoring of species assemblages using environmental DNA (Barnes & Turner, 2016; Thomsen & Willerslev, 2015), and for identifying the origin of animals found in wild meat markets and the illegal pet trade (Cardeñosa et al, 2021; Maligana et al, 2020; Russello et al, 2008). However, many of these methods are reliant on databases from which sequences can be integrated and against which results can be compared, and which are often incomplete (Curry et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the absence of spatial genetic structure, our phylogenetic analyses showed that M. francoismoutoui has diversified into at least five deeply divergent mtDNA lineages, Diversification of an island endemic bat that are found in sympatry at the level of roost sites, including maternity roosts. Sympatric mtDNA lineages are not commonly described in animals, and especially in bats (Andriollo et al, 2015;Sun et al, 2016) and their origin and maintenance are often difficult to resolve (Hogner et al, 2012;Makhov et al, 2021;Webb et al, 2011). This may be explained by stochastic lineage sorting processes that occur in panmictic populations with large effective population size (Hogner et al, 2012;Webb et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our personal unpublished data suggest that such patterns of selective infection can be found in other Colias taxa, presumably being a general characteristic of the genus. It also should be noted that a surprisingly low number of publications devoted to analysis of Wolbachia infection in Lepidoptera consider Wolbachia prevalence in males and females independently [130,131], while the sex-dependent impact of Wolbachia on its hosts is highly expected.…”
Section: Wolbachia Infection In C Mongola/c Tamerlanamentioning
confidence: 99%